Neurophysiology of speech differences in childhood apraxia of speech - Preston, Jonathan L; Molfese, Peter J; Gumkowski, Nina; Sorcinelli, Andrea; Harwood, Vanessa; Irwin, Julia; Landi, Nicole (Developmental Neuropsychology, 2014)
Event-related potentials (ERPs) were recorded during a picture naming task of simple and complex words in children with typical speech and with childhood apraxia of speech (CAS). Results reveal reduced amplitude prior to speaking complex (multisyllabic) words relative to simple (monosyllabic) words for the CAS group over the right hemisphere during a time window thought to reflect phonological encoding of word forms. Group differences were also observed prior to production of spoken tokens regardless of word complexity during a time window just prior to speech onset (thought to reflect motor planning/programming). Results suggest differences in pre-speech neurolinguistic processes.
Keywords: Adolescent; Apraxias; Child; Evoked Potentials; Female; Humans; Linguistics; Male; Neurophysiology; Speech; adolescent; apraxia; article; child; comparative study; dept.cmd; dept.psy; evoked response; female; human; linguistics; male; neurophysiology; pathophysiology; physiology; speech

Electrophysiology of perception and processing of phonological information as indices of toddlers' language performance - Harwood, Vanessa; Preston, Jonathan; Grela, Bernard; Roy, Dooti; Harold, Olivia; Turcios, Jacqueline; Andrada, Kiyomi; Landi, Nicole (Journal of Speech Language and Hearing Research, 2017)
Purpose: The toddler years are a critical period for language development and growth. We investigated how event-related potentials (ERPs) to repeated and novel nonwords are associated with clinical assessments of language in young children. In addition, nonword repetition (NWR) was used to measure phonological working memory to determine the unique and collective contribution of ERP measures of phonemic discrimination and NWR as predictors of language ability. Method: Forty children between the ages of 24-48 months participated in an ERP experiment to determine phonemic discrimination to repeated and novel nonwords in an old/new design. Participants also completed a NWR task to explore the contribution of phonological working memory in predicting language. Results: ERP analyses revealed that faster responses to novel stimuli correlated with higher language performance on clinical assessments of language. Regression analyses revealed that an earlier component was associated with lower level phonemic sensitivity, and a later component was indexing phonological working memory skills similar to NWR. Conclusion: Our findings suggest that passive ERP responses indexing phonological discrimination and phonological working memory are strongly related to behavioral measures of language.
Keywords: Brain; Child Language; Child, Preschool; Discrimination (Psychology); Electroencephalography; Evoked Potentials; Female; Humans; Language Tests; Male; Memory, Short-Term; Pattern Recognition, Physiological; Phonetics; Reaction Time; Regression Analysis; Signal Processing, Computer-Assisted; Speech Perception; adult; brain; child; clinical article; dept.psy; electroencephalography; event related potential; evoked response; female; human; language ability; language development; language test; male; pattern recognition; perception; perceptive discrimination; phonetics; physiology; preschool child; reaction time; regression analysis; short term memory; signal processing; speech perception; stimulus; working memory; young adult; ⚠️ Invalid DOI